Poly[N‐(10‐oxo‐2‐vinylanthracen‐9(10H)‐ylidene)cyanamide] as a novel cathode material for li‐organic batteries. Issue 21 (17th June 2015) - Schmidt, Daniel; Häupler, Bernhard; Stolze, Christian; Hager, Martin D.; Schubert, Ulrich S.
ABSTRACT Redox‐active polymers draw significant attention as active material in secondary batteries during the last decade. A new anthraquinone‐based redox‐active monomer was designed, which electrochemical behavior was tailored by mono‐modification of one keto group. The monomer exhibits two one‐electron redox reactions and has a low molar mass, resulting in a high theoretical capacity of 207 mAh/g. The polymerization of the monomer was optimized by variation of solvent and initiator. Moreover, the electrochemical behavior was studied using cyclic voltammetry and the polymer was used as active material in a composite electrode in lithium organic batteries. The polymer reveals a cell potential of 2.3 V and a promising capacity of 137 mAh/g. During the first 100 cycles, the capacity drops to 85% of the initial value. The influence of the charging speed on the charging/discharging properties of the batteries was further investigated. © 2015 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2015, 53, 2517–2523